2016
DOI: 10.5603/ep.a2016.0039
|View full text |Cite
|
Sign up to set email alerts
|

Przypadkowo wykryty guz nadnercza (incydentaloma) u dorosłych — zasady postępowania rekomendowane przez Polskie Towarzystwo Endokrynologiczne

Abstract: Introduction: A wide use of imaging techniques results in more frequent diagnosis of adrenal incidenataloma. Aim: To analyse the current state of knowledge on adrenal incidentaloma in adults in order to prepare practical management recommendations. Methods: Following a discussion, the Polish Society of Endocrinology expert working group have analysed the available data and summarised the analysis results in the form of recommendations. Imaging and hormonal assessment: Unenhanced adrenal computed tomography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 38 publications
1
59
0
2
Order By: Relevance
“…The presence of Cushing’s syndrome was confirmed on the basis of clinical evaluation in terms of clinical symptoms (altered fat distribution, wide purple striae, etc. ), assessment of 24-h urinary cortisol (normal range 12–330 nmol/24 h), serum cortisol levels after suppression test applying 1 mg dexamethasone (DXM) (immunofluorescent assay, concentrations > 140 nmol/L indicated hypercortisolism), and analysis of plasma ACTH levels (normal range 15–46 pg/mL) [41,42]. Fourteen patients had adrenal Cushing’s syndrome due to adrenal adenomas and two patients suffered from pituitary CS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of Cushing’s syndrome was confirmed on the basis of clinical evaluation in terms of clinical symptoms (altered fat distribution, wide purple striae, etc. ), assessment of 24-h urinary cortisol (normal range 12–330 nmol/24 h), serum cortisol levels after suppression test applying 1 mg dexamethasone (DXM) (immunofluorescent assay, concentrations > 140 nmol/L indicated hypercortisolism), and analysis of plasma ACTH levels (normal range 15–46 pg/mL) [41,42]. Fourteen patients had adrenal Cushing’s syndrome due to adrenal adenomas and two patients suffered from pituitary CS.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of AIs was assessed by determining UFC in 24-h urine and serum cortisol levels after suppression test with DXM using immunofluorescent assay (concentrations < 50 nmol/L excluded hypercortisolism, intermediate cut-off point of 94 nmol/L indicated subclinical hypercortisolism), dehydroepiandrosterone sulphate (DHEA-S) in serum (normal range equal to 34–430 μg/dL), aldosterone levels in serum and urine, potassium in blood, and methoxycatecholamines in 24-h urine [22,41,42]. The immunochemical assays revealed that AIs were non-hypersecretory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with bilateral hyperplasia are treated with a mineralocorticoid receptor antagonist, whereas the subjects with a unilateral adenoma undergo adrenalectomy [8,9]. Because aldosterone-producing microadenomas and multiple bilateral lesions are often undetectable on computed tomography (CT), there is a substantial risk of misdiagnosis when using only CT scanning [10][11][12][13][14][15][16]. The current guidelines on the management of PA recommend adrenal vein sampling (AVS) as a "gold standard" procedure to differentiate between both subtypes in the majority of patients with PA [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hormonal function of the tumor should also be assessed (evaluation of cortisol and androgen concentrations in serum, evaluation of daily excretion of free cortisol, 17-OH steroids and 17-ketosteroids, metanephrines in urine or blood, aldosterone and renin plasma activity or renin concentration in blood). The best test to exclude subclinical hypercortisolemia is a dexamethasone suppression test [29]. Subclinical form of hypercortisolemia occurs in the case of autonomous cortisol secretion from the tumor, usually at normal cortisol concentrations.…”
Section: Morphological Changes In Adrenal Cortexmentioning
confidence: 99%